2020
DOI: 10.18196/jgpp.72124
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leadership Style and Compensation on the Work Performance of Merangin District Office Employees, Jambi: The Role of Work Motivation

Abstract: The purpose of this study was to examine the effect of leadership style and compensation on work motivation and its implications for the performance of the staff of the Merangin Regency Secretariat, Jambi, Indonesia. Research on 245 respondents from the Merangin Regency Secretariat staff, Jambi, Indonesia. The research method uses descriptive research and survey methods. The analysis model uses SEM (Structural Equation Modeling) analysis. The results showed: (1) There was a positive and significant influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Building good relationships with team members through open communication, cooperation, and mutual trust is the foundation of an effective team that encourages them to contribute enthusiastically and optimally to the success of the team or organization. This finding is similar to studies conducted by Rawung (2013), Noviyanti et al (2019), Nalim et al (2020), andIbrahim et al (2022) who found that leadership has a significant impact on work motivation.…”
Section: Effectsupporting
confidence: 91%
See 1 more Smart Citation
“…Building good relationships with team members through open communication, cooperation, and mutual trust is the foundation of an effective team that encourages them to contribute enthusiastically and optimally to the success of the team or organization. This finding is similar to studies conducted by Rawung (2013), Noviyanti et al (2019), Nalim et al (2020), andIbrahim et al (2022) who found that leadership has a significant impact on work motivation.…”
Section: Effectsupporting
confidence: 91%
“…),Noviyanti et al (2019),Nalim et al (2020) andIbrahim et al (2022) concluded that leadership has a significant impact on work motivation. However, in contrast to the research ofDwipayana et al (2023) stated the result that leadership does not have an impact on work motivation.…”
mentioning
confidence: 99%
“…A study (Endri, 2021) states that compensation has a very significant effect on employee performance. Other studies say that if compensation is increased, it will increase employee performance, meaning that compensation has a positive effect on performance (Muchran, 2020). Research also reinforces this, which states that compensation motivates employees to work optimally in the company (R. Putra, 2021).…”
Section: Perkebunan Nusantara IIImentioning
confidence: 81%
“…The banking business is a competitive field that drives the improvement of service quality to better serve customers compared to competitors [1]. To fulfill their role as intermediaries, banks offer various fund collection products such as current accounts, savings accounts, and deposits, as well as fund allocation products including investment loans, working capital loans, and consumer loans [2].…”
Section: Introductionmentioning
confidence: 99%